Anti-Racism from the Margins : Welcoming Refugees at Schengen’s Northernmost Border - Boe, Carolina S.; Horsti, Karina (Palgrave Macmillan, 2018)
Through events of solidarity with refugees that unfolded at the Arctic border between Norway and Russia in 2015, we critically address two common analyses of racism and humanitarianism. First, we argue that the often-claimed explanation that racism results from disenfranchised social class fails to identify solidarities across marginalized groups. Furthermore, as anti-Muslim racism has become more mainstream in the Nordic region, solidarity with refugees offers critical positions in relation to political centers. Second, the case demonstrates how humanitarian action and politicized refugee activism are not necessarily separate forms of action but more entangled forms of engagement. The case where a small Arctic community in Kirkenes responded in solidarity with the refugees who crossed the border from Russia demonstrates how humanitarian assistance entangles with politicized action against the European border regime and against xenophobia, which the locals perceive to be generated by politicians from the political centers of Europe. peerReviewed